The Effect of Feeding Duck Mie (Innovation in Noodle-shaped Duck Feed) on Income Over Feed Cost - Sukarne Sukarne; Muhammad Nursan (Jurnal Biologi Tropis, 2022)
Low feed efficiency is often an obstacle in duck farming. Thus, the duck feed in the form of noodles (duck mie) is innovated which resembles earthworms which is the natural food for ducks in their natural habitat (rice fields and swamp areas). The aim of this study was to determine the extent to which the provision of duck mie in the ration affects the productivity of Peking ducks. This research used a completely randomized design (CRD) method with 4 treatments and replicated four times each, the research material in the form of 80 DOD peking ducks with treatment aged 1-7 days given 100% basal formulated feed. Age 8-14 days adapted to 95% basal formulated feed + 5% Duck Mie. Age 15 – 56 days of basal formulated feeding according to treatment T0 = 100% basal formulated feed, T1 = 90% basal formulated feed + 10% Duck Mie, T2 = 80% basal formulated feed + 20% Duck Mie, and T3 = 70% basal formulated feed + 30 % Duck Mie. The research results were analyzed using analysis of variance (ANOVA), then tested using Duncan's Distance Test. The research parameters were feed consumption, daily body weight gain (DBWG), feed efficiency, feed conversion and IOFC (Income Over Feed Cost). Based on the research conducted, it was found that giving Duck Mie in the ration did not have an effect (P<0.05) on consumption, DBWG, feed efficiency and feed conversion, but had a very significant effect on the IOFC value (P>0.01).